DUNIA DALAM DIRI: ASPEK LINGUISTIK SAJAK-SAJAK UMBU LANDU PARANGGI - sujaya, made (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 17 No 1 (2017)DO - 10.24843/PJIIB.2017.v17.i01.p02, 2017)
The article reveals the linguistic aspects in Umbu Landu Paranggi’s rhymes. With structural approach and stylistic method, the analysis of linguistic aspects included phonology, morphology, syntax and semantics. The results of the analysis of Umbu’s rhymes showed the tendency of strong dynamics, in terms of form, phonology, morphology, syntax and semantics. Umbu truly utilized the wealth and possibilities the language has to build up poetic e?ects in his rhymes. Semantically, Umbu’s rhymes implied the messages about ‘the world within the self’. With the choices of themes, idioms and language styles that prioritized silence, love and longing, Umbu conveyed the message about the importance of holding dialog with the self in interpreting all life dynamics.   Keywords : linguistic aspects, rhymes